Enhanced Gradation Guidelines to Improve Asphalt Mixture Performance. Issue 1 (January 2014) - Greene, James; Chun, Sanghyun; Choubane, Bouzid
In 2010 a theoretical approach to the evaluation and specification of aggregate gradations to resist rutting was evaluated by the Florida Department of Transportation by accelerated pavement testing. This approach, known as the dominant aggregate size range (DASR) gradation model, provides a framework to ensure that the coarse aggregate of the resulting mixture has sufficient aggregate interlock to resist permanent deformation. Further research by the University of Florida and the Department of Transportation found that the properties of the interstitial components (ICs) within the DASR voids were strongly related to the durability and fracture resistance of asphalt mixtures. Parameters that made up the combined DASR-IC model included the DASR porosity, disruption factor (DF), effective film thickness (EFT), and fine aggregate ratio (FAR). The original evaluation of the DASR model was recently extended to include DASR gradations that might have had marginal aggregate interlock (i.e., marginal DASR porosity) and the effect of IC properties on mixture fracture resistance. The results confirmed that the rutting performance of the asphalt mixture was primarily controlled by the DASR porosity and that mixtures with marginal DASR porosity might still have had significantly better rutting performance than mixtures with poor DASR porosity. In addition, it was shown that the DASR porosity, DF, EFT, and FAR parameters played a critical role in mixture cracking performance. The validation of the combined DASR–IC model was documented, and the acceptable range of each parameter for improved mixture rutting and cracking performance was confirmed.